DEVELOPMENT OF CHILDREN AND TEENAGERS SPORTS SCHOOLS VOLLEYBALL PLAYERS JUMPING AND JUMPING ENDURANCE: DEVELOPMENT OF CHILDREN AND TEENAGERS SPORTS SCHOOLS VOLLEYBALL PLAYERS JUMPING AND JUMPING ENDURANCE - Hasanov, anvar (Физическое воспитание, спорт и здоровье, 2022)
This article discusses the problems of developing the qualities of jumping and jump endurance of volleyball players of children and youth sports schools.